B7-Positive and B7-Negative Acute Myeloid Leukemias Display Distinct T Cell Maturation Profiles, Immune Checkpoint Receptor Expression, and European Leukemia Net Risk Profiles - Antohe, Ion; Dǎscǎlescu, Angela; Dǎnǎilǎ, Cǎtǎlin; Titieanu, Amalia; Zlei, Mihaela; Ivanov, Iuliu; Sireteanu, Adriana; Pavel, Mariana; Cianga, Petru (Frontiers in Oncology, 2020)
Acute myeloid leukemia (AML) is generally considered a poorly immunogenic malignancy, displaying a “non-inflamed” leukemia microenvironment, leading to T cell tolerance. However, the immune landscape of AML is much more heterogeneous. Since B7 expression is regarded as a consequence of an interferon-mediated “inflammatory” phenotype, we have investigated by flow cytometry the B7 checkpoint ligands B7.1, B7.2, PD-L1, PD-L2, ICOS-L, B7-H3, B7-H4 on the AML blasts of 30 newly diagnosed patients, and their corresponding receptors (CTLA-4, PD-1 and ICOS) on bone marrow T cell maturation populations. We could thus evidence B7 negative and B7 positive leukemias, either with an isolated expression, or part of eight different checkpoint ligand “signatures” that always included an inhibitory B7 molecule. B7 positive AMLs encompassed intermediate and adverse ELN risk cases and displayed mainly central memory CD4+ T cells with high ICOS levels, and effector CD8+ T cells with high PD-1 expression. B7 negative cases were rather classified as AML with recurrent genetic anomalies and displayed predominantly naïve T cells, with the exception of NPM1 mutated AMLs, which expressed B7-H3. These different B7 immune profiles suggest that specific immunotherapies are required to target the distinct immune evasion strategies of this genetically heterogeneous disease.